Pendidikan Sosial Sesuai Hadits Rosul SAW - suluri, suluri (BELAJEA: Jurnal Pendidikan Islam, 2019)
This paper examines various social problems in society often occur. In interacting with the community, like it or not, like it or not, intentionally or unintentionally it often happens that the offense and hurt hurt. The Prophet Muhammad as the messenger of Allah who was sent to perfect morality has set examples in navigating life in the world, especially in social matters. Evidently Rosul SAW has built a civil society in Medina. The examples of the Prophet Muhammad who I adopted in this article are the prohibition of whispering together without regard to the third, the ethics of visiting, greeting, giving the right of road users and giving rights to neighbors. From these various themes, it is expected to be a learning so that in interacting with fellow human beings, a Muslim always prioritizes morality.